PLA / PHA biodegradable composite fiber and preparation method thereof

By introducing PHA-g-MA and compatible agent into PLA/PHA composite materials to form a micro-crosslinked structure, the problem of poor compatibility after improving PHA components is solved, and the spinning stability and thermal drafting performance are improved. In high-end textile and medical products.

CN119265748AInactive Publication Date: 2025-01-07SHANGHAI YINGHUA CHENRUI NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411562547.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The compatibility of the two items after the PHA components are improved in PLA/PHA composite system is poor, resulting in a decrease in spinning processing stability and thermal drafting performance.

Method used

The reactive compatibilizer PHA-g-MA and compatibilizers such as DCP and BIBP are introduced to form a micro-crosslinked structure to improve the compatibility and heat resistance of PLA and PHA.

Benefits of technology

It improves the compatibility and spinning stability of the PLA/PHA system, enhances the thermal drafting and heat resistance of the fiber, broadens the spinning processing window, and is suitable for high-end textile and medical products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265748A_ABST
    Figure CN119265748A_ABST
Patent Text Reader

Abstract

The invention discloses a PLA (polylactic acid) / PHA (polyhydroxyalkanoate) biodegradable composite fiber and a preparation method thereof, and the PLA / PHA biodegradable composite fiber is prepared from the following components in parts by mass: 70 to 95 parts of PLA, 5 to 30 parts of PHA, 1 to 5 parts of PHA-g-MA (polyhydroxyalkanoate-g-MA), 0.2 to 1 part of antioxidant, 0.1 to 1 part of compatilizer and 0.1 to 1 part of lubricant. According to the invention, the problem of poor compatibility of two items after PHA components in a PLA / PHA composite material system are improved is mainly solved, a micro-crosslinking structure can be formed at a phase interface of the PLA-PHA system by introducing the reactive compatilizer component, the compatibility of the two items is improved, the heat resistance of the material is also improved, and the material has good stability and hot drawing performance during rear-end spinning.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of biodegradable fiber textiles, and in particular to a PLA / PHA biodegradable composite fiber and a preparation method thereof. Background Art

[0002] As people's environmental awareness continues to increase, biodegradable materials have begun to appear in various fields of our lives. Biodegradable materials have developed from traditional injection molding, film materials, sheet materials and other fields to high-end fields such as rubber and textiles. At present, in the field of biodegradable fiber textiles, polylactic acid (PLA), polybutylene adipate / terephthalate (PBAT), polybutylene succinate (PBS), polycaprolactone (PCL), polyhydroxyalkanoate (PHA) and other materials are used as the main raw materials. Among them, PLA, as a biological source, has full biodegradability and good biocompatibility, skin affinity, antibacterial properties, and breathability. Therefore, such products can be used in high-end textile products, medical products, sanitary products and other fields. However, single-component PLA fibers still have some limitations. Their brittleness and poor thermal stability limit their further application in spinning processing. Therefore, PHA is introduced into PLA for blending and modification to obtain fibers with better comprehensive performance. However, the preparation process of PHA-containing fibers often encounters problems such as slow crystallization rate and poor compatibility.

[0003] Chinese patent CN 114318588A discloses a PLA / PHA composite fiber. The patent uses PHA (P4HB) and PLA to blend, and combines reactive and physical compatibilizers for modification, so that the compatibility of the two materials is greatly improved, which helps to improve the toughness and strength of the fiber. Among them, PHA accounts for a large proportion. The second drafting temperature is not high during processing, which will lead to serious post-crystallization of the system, resulting in brittleness and decreased mechanical properties. Chinese patent CN 114262952A discloses a composite material and its preparation method and application, which mainly uses nylon and PHA as the core structure and skin structure of the composite skin-core structure, so that it has the high strength characteristics of nylon and the degradable characteristics of PHA, but the processing temperature difference between nylon and PHA is large, the spinning stability is poor, and nylon is a non-degradable material. Chinese patent CN 102392318A discloses a bio-based degradable fiber and a preparation method thereof, wherein the fiber is obtained by blending and modifying two materials, PLA and PHBV. Since the two materials are simply blended without compatibility modification, the material compatibility and heat resistance are poor. Summary of the invention

[0004] The present invention mainly solves the problem that the PHA component in the PLA / PHA composite material system has poor compatibility after the two compatibilities are improved. By introducing a reactive compatibilizer component, a micro-crosslinking structure can be formed at the interface of the PLA-PHA system to improve the compatibility of the two components, and the heat resistance of the material is also improved, so that the material has better stability and thermal drawing performance during the back-end spinning.

[0005] The present invention is implemented by the following technical solutions:

[0006] A PLA / PHA biodegradable composite fiber comprises the following components by weight: 70-95 parts of PLA, 5-30 parts of PHA, 1-5 parts of PHA-g-MA, 0.2-1 parts of antioxidant, 0.1-1 parts of compatibilizer and 0.1-1 parts of lubricant.

[0007] Furthermore, the PLA structure is one or two or more of L and D type polylactic acid, with a melt index of 5-30 g / 10 min (190° C., 2.16 kg); preferably Total series LX175, L130, D70 series.

[0008] Furthermore, the PHA comprises one or more of 3-hydroxypropionic acid, 3-hydroxybutyric acid, 3-hydroxyvaleric acid, 3-hydroxyhexanoic acid, 4-hydroxybutyric acid and 5-hydroxyvaleric acid, and has a melt index of 2-10 g / 10 min (165° C., 2.16 kg); preferably, the PHA is PHBH, BP350, BP330 series produced by Blue Crystal Microbiology Company.

[0009] Furthermore, the PHA-g-MA is obtained by independent synthesis, using dichloromethane as a solution and BPO as an initiator to graft MA onto PHA, with a grafting rate between 1.0% and 1.3%.

[0010] Furthermore, the synthesis route of the PHA-g-MA is specifically as follows: 54.0 g of PHA is dissolved in 240 mL of dichloromethane, 6.0 g of MA and 1.8 g of BPO are added to the solution in four times, and the reaction is stirred at 85±2° C. for 12 hours in a nitrogen atmosphere, and the reaction product is refluxed and dissolved in 200 mL of dichloromethane, and then the solution is filtered through cotton cloth and the cotton cloth is placed in a vacuum oven at 80±1° C. for evaporation for 24 hours; the product on the cotton cloth is washed with acetone to remove unreacted MA, and the dichloromethane-soluble product in the filtrate is extracted with 600 mL of cold acetone; the grafting rate of the obtained PHA-g-MA product is calculated to be 1.05%.

[0011] Furthermore, the antioxidant is an amine antioxidant or a phosphite antioxidant, specifically one or two or more of antioxidant 1010, antioxidant 168, and antioxidant 1076, preferably antioxidant 1010 and antioxidant 168.

[0012] Furthermore, the compatibilizer is one or two or more of triallyl isocyanurate (TAIC), cumene peroxide (DCP), benzoyl peroxide (BPO), di-tert-butyl peroxy isopropyl benzene (BIBP), and 2,5-dimethyl-di(tert-butyl peroxy) hexane (bis-25), preferably cumene peroxide (DCP), di-tert-butyl peroxy isopropyl benzene (BIBP), and 2,5-dimethyl-di(tert-butyl peroxy) hexane (bis-25).

[0013] Furthermore, the lubricant is one or two or more of erucamide, oleamide, and stearic acid amide, preferably erucamide and stearic acid amide.

[0014] The present invention also discloses a method for preparing the PLA / PHA biodegradable composite fiber, comprising the following steps:

[0015] S1. The raw materials of each component are weighed and added to a high mixer for mixing, mixed at 200-400rpm at 50-65°C for 1-5min, mixed evenly and added to the hopper of a twin-screw extruder, melt extruded and drawn out from the outlet of the die head, cooled and pelletized to obtain PLA / PHA composite slice particles, the melt extrusion temperature of the twin-screw extruder is 150-200°C, and the screw speed is 200-400rpm;

[0016] S2. The PLA / PHA composite slice particles are dried in a vacuum strand dryer at 80-100°C for 2-4h to obtain dry slice particles with a moisture content of less than 300ppm, and then the dried slice particles are added to a melt spinning extruder for melt spinning, and full-stretch spinning is directly performed at a spinning temperature of 150°C-200°C, a spinning extrusion rate of 5-30rpm, a drawing ratio of 2-4 times, a hot drawing temperature of 70-110°C, and a drawing speed of 500-2000m / min to obtain PLA / PHA biodegradable composite fibers.

[0017] Beneficial effects of the present invention:

[0018] 1. Due to the poor compatibility between PLA and PHA, the resin compatibility is improved by adding PHA-g-MA. The strong polar groups on the surface of PHA maleic anhydride grafts can greatly improve the compatibility of the material, thereby improving the stability of the back-end spinning. The compatibility of the two phases in the PLA / PHA system is further improved by introducing compatibilizers such as DCP and BIBP. As the PHA component increases, the introduced compatibility can form a micro-cross-linked structure between the PLA / PHA two phases, so the system still has good compatibility, so that the performance improvement is maintained well. After the introduction of compatibilizers such as PHA-g-Ma and DCP between the two phases, the two phases play a synergistic role to a certain extent, making the two-phase structure dense and having good heat resistance, which has certain advantages in the dyeing and rinsing process at the back end of fiber spinning.

[0019] 2. PLA fiber itself has good strength, but insufficient toughness and elasticity in the field of fiber textiles. Therefore, PHA is introduced into it. Due to the poor compatibility caused by the addition of PHA, the compatibility stability of the system is improved by introducing a compatibilizer. The formation of a reactive micro-cross-linked structure not only improves the stability of the subsequent processing of the system, but also broadens the subsequent processing window of the fiber spinning end, improves the requirements for subsequent process treatment, and has certain guiding significance for continuous production spinning. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings are used to provide further explanation of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0021] Figure 1 Schematic diagram of the synthesis reaction of PHA-g-MA. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following embodiments.

[0023] The PHA-g-MA used in the embodiments of the present invention and the comparative examples is obtained by independent synthesis. The synthesis route of PHA-g-MA is to dissolve 54.0g of PHA in 240mL of dichloromethane, add 6.0g of MA and 1.8g of BPO to the solution in four times, stir and react for 12h at 85±2°C in a nitrogen atmosphere, and reflux and dissolve the reaction product in 200mL of dichloromethane. Then, the solution is filtered through cotton cloth and the cotton cloth is placed in a vacuum oven at 80±1°C for evaporation for 24h. The product on the cotton cloth is washed with acetone to remove unreacted MA, and the dichloromethane-soluble product in the filtrate is extracted with 600mL of cold acetone. The grafting rate of the obtained PHA-g-MA product is calculated to be 1.05%.

[0024] Example 1

[0025] The raw materials were prepared according to the components of Example 1 described in Table 1. PLLA, PHBH, PHA-g-MA, DCP and the additives were stirred at 60°C and 300rpm for 3min in a high mixer to mix evenly, and then the mixed raw materials were added to the hopper of a twin-screw extruder. The extrusion temperature of the twin-screw extruder was set to 175°C and the screw speed was 250rpm. After the twin-screw was melted and extruded, PLA / PHA composite modified particles were obtained after drawing, traction, cooling and pelletizing. The modified particles were dried in a vacuum strand dryer at 100°C for 4h, and then spun by a melt spinning machine. The spinning temperature was 165 / 170 / 180 / 190 / 195 / 195 / 195, the extrusion rate was 30rpm, the draft ratio was 3.0, the hot drafting temperature range was 60 / 80°C / 100°C, the drafting rate range was 1000 / 3000 (m / min), and the fiber bundle size was 100D / 48f.

[0026] Example 2

[0027] The raw materials were prepared according to the components of Example 2 shown in Table 1. PLLA, PHBH, PHA-g-MA, BI BP, additives and talc were mixed evenly in a high-speed mixer, and then the mixed raw materials were added to the hopper of a twin-screw extruder. The extrusion temperature of the twin-screw extruder was set at 175°C, and the twin-screws were melted and extruded. After drawing, traction, cooling and pelletizing, the modified particles were obtained. The fiber spinning steps were the same as those in Example 1.

[0028] Embodiment 3:

[0029] The raw materials were prepared according to the components of Example 3 shown in Table 1. PLLA, PHBH, PHA-g-MA, double 25 and the additives were mixed evenly in a high-speed mixer, and then the mixed raw materials were added to the hopper of the twin-screw extruder. The extrusion temperature of the twin-screw extruder was set to 175°C, and the twin-screw was melted and extruded. After drawing, traction, cooling and pelletizing, the modified particles were obtained. The fiber spinning steps were the same as in Example 1.

[0030] Embodiment 4:

[0031] The raw materials were prepared according to the components of Example 4 shown in Table 1. PLLA, PDLA, PHBH, PHA-g-MA, BIBP, double 25 and the additives were mixed evenly in a high-speed mixer, and then the mixed raw materials were added to the hopper of the twin-screw extruder. The extrusion temperature of the twin-screw extruder was set to 175°C, and the twin-screw was melted and extruded. After drawing, traction, cooling, and pelletizing, the modified particles were obtained. The fiber spinning steps were the same as in Example 1.

[0032] Embodiment 5:

[0033] The raw materials were prepared according to the components of Example 5 shown in Table 1. PLLA, PDLA, PHBH, PHA-g-MA, DCP, bi-25 and other additives were mixed evenly in a high-speed mixer, and then the mixed raw materials were added to the hopper of a twin-screw extruder. The extrusion temperature of the twin-screw extruder was set to 175°C, and the twin-screw was melted and extruded. After drawing, traction, cooling, and pelletizing, the modified particles were obtained. The fiber spinning steps were the same as in Example 1.

[0034] Comparative Example 1:

[0035] The raw materials were prepared according to the components of comparative example 1 shown in Table 1. The PLLA resin was mixed evenly with DCP, antioxidant, etc. by a high-speed mixer, and then the mixed raw materials were added to the hopper of a twin-screw extruder. The extrusion temperature of the twin-screw extruder was set to 175°C, and the twin-screw was melted and extruded. After drawing, traction, cooling, and pelletizing, the modified particles were obtained. The fiber spinning steps were the same as those in Example 1.

[0036] Comparative Example 2:

[0037] The raw materials were prepared according to the composition of comparative example 2 shown in Table 1. PLLA, PHBH, PHA-g-MA and additives such as antioxidants were mixed evenly in a high-speed mixer, and then the mixed raw materials were added to the hopper of a twin-screw extruder. The extrusion temperature of the twin-screw extruder was set at 175°C, and the twin-screws were melted and extruded. After drawing, traction, cooling, and pelletizing, the modified particles were obtained. The fiber spinning steps were the same as those in Example 1.

[0038] Comparative Example 3:

[0039] The raw materials were prepared according to the composition of comparative example 3 shown in Table 1. PLLA, PHBH, PHA-g-MA, antioxidants, lubricants and other additives were mixed evenly in a high-speed mixer, and then the mixed raw materials were added to the hopper of a twin-screw extruder. The extrusion temperature of the twin-screw extruder was set to 175°C, and the twin-screw was melted and extruded. After drawing, traction, cooling, and pelletizing, the modified particles were obtained. The fiber spinning steps were the same as those in Example 1.

[0040] Comparative Example 4:

[0041] The raw materials were prepared according to the composition of comparative example 4 shown in Table 1. PLLA, PHBH, BIBP, antioxidants, lubricants and other additives were mixed evenly in a high-speed mixer, and then the mixed raw materials were added to the hopper of a twin-screw extruder. The extrusion temperature of the twin-screw extruder was set at 175°C, and the twin-screws were melted and extruded. After drawing, traction, cooling, and pelletizing, the modified particles were obtained. The fiber spinning steps were the same as those in Example 1.

[0042] Table 1: Examples and Comparative Examples

[0043]

[0044]

[0045] Table 2: Test results of composite fiber performance of examples and comparative examples

[0046]

[0047] Finally, it should be noted that the above-mentioned embodiments only express several implementation methods of the present invention and are not intended to limit the invention. For those skilled in the art, any modification, equivalent replacement, improvement, etc. made without departing from the concept of the present invention should be included in the protection scope of the invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A PLA / PHA biodegradable composite fiber, characterized in that: The composition comprises the following components in parts by mass: 70-95 parts of PLA, 5-30 parts of PHA, 1-5 parts of PHA-g-MA, 0.2-1 parts of antioxidant, 0.1-1 parts of compatibilizer and 0.1-1 parts of lubricant.

2. The PLA / PHA biodegradable composite fiber according to claim 1, characterized in that: The PLA structure is one or two or more of L and D type polylactic acid, with a melt index of 5-30 g / 10 min (190° C., 2.16 kg); preferably, Total series LX175, L130, D70 series.

3. The PLA / PHA biodegradable composite fiber according to claim 1, characterized in that: The PHA comprises one or more of 3-hydroxypropionic acid, 3-hydroxybutyric acid, 3-hydroxyvaleric acid, 3-hydroxyhexanoic acid, 4-hydroxybutyric acid and 5-hydroxyvaleric acid, and has a melt index of 2-10 g / 10 min (165° C., 2.16 kg); preferably, the PHA is PHBH, BP350, BP330 series produced by Blue Crystal Microbiology Company.

4. The PLA / PHA biodegradable composite fiber according to claim 1, characterized in that: The PHA-g-MA is synthesized independently, using dichloromethane as a solution and BPO as an initiator to graft MA onto PHA, with a grafting rate between 1.0% and 1.3%.

5. The PLA / PHA biodegradable composite fiber according to claim 4, characterized in that: The synthesis route of the PHA-g-MA is specifically as follows: 54.0 g of PHA is dissolved in 240 mL of dichloromethane, 6.0 g of MA and 1.8 g of BPO are added to the solution in four times, and the reaction is stirred at 85±2° C. for 12 hours in a nitrogen atmosphere, and the reaction product is refluxed and dissolved in 200 mL of dichloromethane, and then the solution is filtered through cotton cloth and the cotton cloth is placed in a vacuum oven at 80±1° C. for evaporation for 24 hours; the product on the cotton cloth is washed with acetone to remove unreacted MA, and the dichloromethane-soluble product in the filtrate is extracted with 600 mL of cold acetone; and the grafting rate of the obtained PHA-g-MA product is calculated to be 1.05%.

6. The PLA / PHA biodegradable composite fiber according to claim 1, characterized in that: The antioxidant is an amine antioxidant or a phosphite antioxidant, specifically one or two or more of antioxidant 1010, antioxidant 168, and antioxidant 1076, preferably antioxidant 1010 and antioxidant 168.

7. The PLA / PHA biodegradable composite fiber according to claim 1, characterized in that: The compatibilizer is one or two or more of triallyl isocyanurate, cumene peroxide, benzoyl peroxide, di-tert-butyl peroxy isopropyl benzene, and 2,5-dimethyl-di(tert-butyl peroxy)hexane, preferably cumene peroxide, di-tert-butyl peroxy isopropyl benzene, and 2,5-dimethyl-di(tert-butyl peroxy)hexane.

8. The PLA / PHA biodegradable composite fiber according to claim 1, characterized in that: The lubricant is one or two or more of erucamide, oleamide and stearic acid amide, preferably erucamide and stearic acid amide.

9. A method for preparing the PLA / PHA biodegradable composite fiber according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. The raw materials of each component are weighed and added to a high mixer for mixing, mixed at 200-400rpm at 50-65°C for 1-5min, mixed evenly and added to the hopper of a twin-screw extruder, melt extruded and drawn out from the outlet of the die head, cooled and pelletized to obtain PLA / PHA composite slice particles, the melt extrusion temperature of the twin-screw extruder is 150-200°C, and the screw speed is 200-400rpm; S2. The PLA / PHA composite slice particles are dried in a vacuum strand dryer at 80-100°C for 2-4h to obtain dry slice particles with a moisture content of less than 300ppm, and then the dried slice particles are added to a melt spinning extruder for melt spinning, and full-stretch spinning is directly performed at a spinning temperature of 150°C-200°C, a spinning extrusion rate of 5-30rpm, a drawing ratio of 2-4 times, a hot drawing temperature of 70-110°C, and a drawing speed of 500-2000m / min to obtain PLA / PHA biodegradable composite fibers.

Citation Information

Patent Citations

  • Biobased biodegradable fiber and preparation method thereof

    CN102392318A

  • Composite material as well as preparation method and application thereof

    CN114262952A

  • Completely biodegradable polyhydroxyalkanote / polycarbonate blending alloy and preparation thereof

    CN101475734A

  • Plant fiber and PHA (polyhydroxyalkanoate) composite oil-absorbing sheet and preparation method thereof

    CN105155351A

  • Poly (4-hydroxybutyrate) / polylactic acid blend fiber and preparation method thereof

    CN114318588A

Cited By

  • Environment-friendly degradable composite film and preparation method thereof

    CN120039010A

  • Biodegradable antibacterial modified composite fiber material and preparation method thereof

    CN120330913A